The NLP Revolution: Transforming Clinical Documentation and Medical Coding - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The healthcare industry, a domain fundamentally reliant on accurate and timely information, faces a persistent challenge: the vast majority of clinical data ...
Keywords: Digital Health; Diagnostics; Healthcare Data; Artificial Intelligence